Effect of Variations in Blood Component Supplementation on the Suitability of Blood Agar Plate Media for the Growth of Salmonella typhi - Fransisca Probo Setyoningrum (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to evaluate the effect of different human blood components added to Blood Agar Plate (BAP) media on the growth of Salmonella typhi O. An experimental design was employed with three treatment groups and a total of 27 replicates. Salmonella typhi O was inoculated onto BAP media containing different blood components, followed by incubation at 37°C for 24 hours. Bacterial colonies were then counted using the total plate count method. Statistical analysis was performed using the Shapiro–Wilk test and one-way ANOVA, followed by Bonferroni post hoc analysis. The results showed that variation in blood components significantly affected colony counts (p = 0.0001). Whole blood containing antibodies produced the lowest bacterial growth (mean 2.6 × 10⁵ CFU/mL), whereas erythrocyte suspension (1.8 × 10⁶ CFU/mL) and whole blood without antibodies (1.9 × 10⁶ CFU/mL) showed substantially higher growth and did not differ significantly from each other (p = 0.618). These findings indicate that antibodies in human blood can inhibit the growth of Salmonella typhi through complement activation, while washed erythrocytes are effective as a substitute for sheep blood. Therefore, whole blood without antibodies or erythrocyte suspension may serve as viable and effective alternatives for the preparation of BAP media in laboratories with limited access to sheep blood.